جودة الحياة الأكاديمية أثناء جائحة كرونا من وجهة نظر الطالب/ة بجامعة طيبة: Quality of Academic Life during COVID-19 Pandemic as Perceived by Taibah University Students - Areej Yousef Ahmed Hakim (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص هدفت الدراسة الحالية إلى التعرف على مستوى جودة الحياة الأكاديمية أثناء جائحة كرونا من وجهة نظر الطالب/ة الجامعي بجامعة طيبة فرع ينبع. ولتحقيق هدف الدراسة استخدم المنهج الوصفي للإجابة عن السؤال الرئيس التالي: ما مستوى جودة الحياة الأكاديمية أثناء جائحة كرونا من وجهة نظر الطالب/ة الجامعي بجامعة طيبة؟ وبتطبيق أداة الدراسـة على عينة الدراسة المكونة من (187 طالب/ة). اسفرت النتائج عن التالي: في محور جودة الممارسة الأكاديمية، إن المتوسط الحسابي العام للمحور هو 4.15 والانحراف المعياري 1.03 مما يدل أن جودة الممارسة الأكاديمية عالية، وحصلت العبارة رقم 9 (قيم الاجراءات الاحترازية التي قدمت لك بتفعيل التعليم عن بعد كبديل للحضور في الحرم الجامعي أثناء جائحة كرونا) على أعلى ترتيب حيث سجلت متوسط حسابي رقم 4.63، بينما سجل المحور الثاني الخاص بمستوى الرضا الأكاديمي متوسط حسابي عام هو 1.76 وانحراف معياري 1.10 مما يدل أن مستوى الرضا الأكاديمي كان بنسبة 58.71% وحصلت العبارة رقم 6 (شعرت بازدياد حبي للوطن أثناء جائحة كرونا) على أعلى ترتيب حيث سجلت متوسط حسابي 4.63 وانحراف معياري قدره 81. وبنسبة 98.93%، وسجل محور المساندة الأكاديمية متوسط حسابي عام هو 4.33 وانحراف معياري 93. مما يدل أن مستوى المساندة الأكاديمية المقدمة للطالب/ة الجامعي أثناء جائحة كرونا كان بنسبة 86.65% وبتقدير (ممتاز) والعبارة رقم 5 (حدد مدى استفادتك من الارشاد الأكاديمي المقدم لك أثناء أزمة كرونا) على أعلى ترتيب بمتوسط حسابي 4.67 وانحراف معياري قدره 72. وبنسبة 93.48%، وتمثلت أغلب الصعوبات التي واجهتهم بالتدريج من الأكثر تأثيرا إلى الأقل في ضعف شبكة الانترنت ثم عدم توفر حاسب شخصي ثم ضعف الخبرات في التعامل مع البلاك بورد ثم ضعف الخبرات التقنية. Abstract The current study aimed to identify the quality level of academic life during COVID-19 pandemic from students' perception of Taibah University, Yanbu branch. To this end, a descriptive approach was used to answer the following main research question: What is the quality level of academic life during COVID-19 pandemic from students' perception of Taibah University? The study tool consisted of a questionnaire to measure the quality level of the students’ academic life. The tool was ensured for reliability and validity and composed of three sections that contained indicators to measure the quality of academic life; academic practices, academic satisfaction, and academic support. The sample of the study consisted of 187 male and female students. Results showed high perceptions for the respondents in the quality of academic practices section (M=4.15, SD=1.03). The statement No.9 entitles “Rate the precautionary actions provided to you to activate the online education as an alternative to face-to-face education during COVID-19 pandemic” obtained the highest rank (M=4.63). The second section that measured the level of academic satisfaction recorded (M=1.76, SD=1.10), obtaining 58.71%. The statement 6 entitles “I felt my love to home increased during COVID-19 pandemic” obtained the highest rank (M=4.63, SD=.81, 98.93%). The academic support dimension recorded (M=4.33, SD=.93), Indicating that the level of academic support for students during COVID-19 pandemic was excellent (86.65%) as perceived by the study sample. The statement 5 which entitles “Rate the extent to benefit from academic counseling during COVID-19 pandemic” got the highest rank (M=4.67, SD=.72, 93.485). The most challenges encountered the students gradually categorized from the highest to the lowest were the poor Internet network, non-availability of laptop computers, low experience in working with blackboard, and poor technical experience. The study recommended the significance of academic support and suggested doing further studies on and the reality of quality of academic life from faculty members perspectives and the role of precautionary health during COID-19 pandemic to enhance the national loyalty for the university students.